Study of some biomechanical variables for the skill of the frontal pneumatic pellet on the balance beam for female girls - Muhammed Ali Hammed, AbdAlSattar; Ehsan Muhammad, Karar; ABdulQader Abdul Sattar, Noor (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to identify variables in biokinetics that own skill in the heart, aerobic front, and aureus device model balance for young women. On a group of six Egyptian women’s national team players of the same age and training level, the researcher relied on photographing and analyzing the skill to extract strengths and weaknesses for the players regarding the skill. Including the researcher concluded that swinging the arms forward high during the tide stage leads to an increase in the height of the center of gravity of the body by a few centimeters before starting to launch, and accordingly, we notice an increase in the shoulder angle during this stage. Increasing the angle of extension of the legs to get a better height, which led to an increase in the body’s tendency to fall?